Contribution to the study the nitrates leaching in the soil surrounding Lake Al-Sin and the factors affecting leaching of Nitrate - محلا ضياء; هيثم شاهين; محمد غفر; ماهر دعيس (Latakia University Journal -Engineering Sciences Series, 2022)
In this study, the process of leaching of nitrate was evaluated. We studied the climatic and topographical factors of the Al-Sin area, and the role of the soil properties of the studied areas in the Al-Sin Spring area on the process of nitrate leaching in the soil horizons. The study found a discrepancy in the leaching of nitrate between the studied sites and between the horizons of the soil of the studied sites, where the sites of Beit Aana, Al-Qutaibiya and Al-Waha Spring were characterized by high levels of leaching, where the highest concentration of nitrate leaching was in the months of November and April, which ranged (56-72) mg/l. and the lowest in the months of January and February ranged (32-40) mg/l, while it was in the sites Bastweer, Beit Al-Aloni, Gebul, and Al-Rahbeya with lower levels of leaching. The highest concentration of nitrate leaching was in the months of November and April, which ranged (34-41) mg /l and the lowest in the months of January and February ranged (16-24) mg/l. The levels of nitrate leaching increase with depth, so that the highest concentrations of nitrate ion leached in the third horizon of the studied sites due to the negative charge of nitrate. The statistical study showed the correlation between the variable N-Leaching with the two variables, the organic matter (OM) and the saturated hydro-hydraulic conductivity (Hy.cond) for the studied sites and horizons, with a high significance that ranged between In the study, we obtained the regression equations that represent the leaching of nitrates in the three horizons and It is concluded that a multiple regression analysis is indispensable in interpreting soil and groundwater NO3- time series of restricted length.